Mathematics excellence for middle school mathematics teachers in Wasit Governorate Mathematics teachers - et. al., Saeed Hussein Hamadallh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current study aimed to identify the levels of mathematics excellence among the middle school mathematics teachers, and verify the study objective , as the researcher adopted the descriptive analytical approach, the study population consisted of male & female teachers of mathematics for the preparatory stage (middle school) belonging to the Wasit Education Directorate, where the size of the research sample was (152) male and female teachers By (71) male teachers and (81) female teachers who specialist in mathematics for middle school and they were distributed to the preparatory and secondary schools in the Directorate of Education in Wasit Governorate, which number is (156) schools, the researcher develop a research tool for the purpose of collecting data of the research that represented in the mathematics excellence test, it consisted of (40) items (14) items from essay type and (26) items from objective type. Statistical analysis of the test items was performed and their psychometric properties were verified , after using the appropriate statistical methods to analyze the results of applying the Mathematics Excellence test on the research sample, the results showed the following results : Male and female teachers have high scores on the Mathematical Excellence Test. The mathematics Excellence drives the behavior of male and female teachers towards perfecting their work, whether academic or in daily life. 3- The gender or years of service do not affect the degree of mathematics Excellence with the level of statistical significance.